Optimization of "#infovaksin" covid-19 as an effort to increase coverage of basic immunization for toddlers during the pandemic - Widya Ratna Wulan; Evina Widianawati; Ika Pantiwati; Edi Jaya Kusuma (Community Empowerment, 2022)
During the Covid-19 epidemic, delays/cessation of vaccination services resulted in a drop in basic immunization coverage for children in Sumampir Village owing to restrictions on direct contact and parental concerns. It is thought that education about the Covid-19 vaccination is crucial in order to avoid new concerns in children's health. This service intends to improve health cadre engagement in Sumampir Village in order to achieve a high level of health. The service technique includes giving vaccinations and Covid-19-related materials and training. This program was successful in strengthening the knowledge and abilities of health personnel in the area of child vaccination. In addition, partners may use their interpersonal communication skills to help the community learn about vaccination and Covid-19 vaccines.